A STUDY ON THE RELATIONSHIP BETWEEN ECOTOURISTS' ENVIRONMENTAL ATTITUDE-BEHAVIOR AND ECOTOURISM ACTIVITIES: THE CASE OF FETHIYE AND ORTACA ECO-FARMS (Third Sector Social Economic Review, 2019)
The need to move away from the stress of city life, the interest in natural and cultural environment has led people to seek alternative tourism. Ecotourism is different from the traditional tourism concept and has attracted the attention of tourists who want to be alone with nature, longing for village life and desire to be intertwined with different cultural environment. Ecotourism is defined as one of the alternative tourism activities. The most important characteristics of tourists participating in ecotourism activities are their sensitivity to nature and cultural environment. In this study, it is aimed to investigate the relationship between ecotourist activity and ecotourism. For this purpose, a field study was conducted for ecotourists in eco-farms located in Fethiye and Ortaca districts of Muğla province. In the field research, survey method was used as data collection technique. 312 ecotourists participated in the survey. The data were tested with correlation analysis. As a result of the study, it was determined that there was a positive and significant correlation between ecotourism activities and ecotourism activities with a positive and negative value of 0,479 and between environmental behaviors and ecotourism activities.
Keywords: Ecotourism; Environmental Attitude; Environmental Behavior